1995
DOI: 10.1074/jbc.270.30.18007
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Stimulation of the Fas-encoding Gene by Nuclear Factor for Interleukin-6 Expression upon Influenza Virus Infection

Abstract: We previously found that the level of Fas, a cell surface receptor for an apoptosis signal, increases at the mRNA level in influenza virus-infected HeLa cells prior to their death by apoptosis. Here we investigated the mechanism of activation of the Fas-encoding gene expression upon influenza virus infection. Nucleotide sequences for the binding of nuclear factor for interleukin-6 expression (NF-IL6), also known as CCAAT/enhancer-binding protein beta, were repeated 8 times in the 5'-end region of the human FAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 54 publications
4
65
2
Order By: Relevance
“…We found that the DNAbinding activity of C/EBP/3 appeared in HL-60 cells after VD3treatment with little change in C/EBP/3 level. Other investigators similarly reported that DNAbinding activity of C/EBP^increased after stimulation, whereas the amount of C/EBP/3 remained unchanged, suggesting that C/EBP/3 was activated through post-translational modification (1,60). Similar post-translational modifi cation of C/EBP/3 may occur in VD3-treated HL-60 cells.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…We found that the DNAbinding activity of C/EBP/3 appeared in HL-60 cells after VD3treatment with little change in C/EBP/3 level. Other investigators similarly reported that DNAbinding activity of C/EBP^increased after stimulation, whereas the amount of C/EBP/3 remained unchanged, suggesting that C/EBP/3 was activated through post-translational modification (1,60). Similar post-translational modifi cation of C/EBP/3 may occur in VD3-treated HL-60 cells.…”
Section: Discussionmentioning
confidence: 73%
“…The antibody stained discrete two protein bands with molecular masses of 46 and 44 kDa; the 44 kDa band was stained much stronger by the antibody. These two proteins are considered to be derived from the first two AUGcodons of C/EBP/3 mRNA (1,60). The intensity of the two signals did not significantly change in HL-60 cells after VD3treatment (Fig.…”
Section: Expression Of Mrp14in Human Monocytic Leukemia Cellsmentioning
confidence: 99%
“…Studies using STAT-1␣-deficient microglia and the specific NF-B inhibitor SN50 prove that STAT-1␣ and NF-B activation are required for IFN-␥-and TNF-␣-mediated Fas induction in microglia, respectively. In HeLa cells, CCAAT/enhancer-binding protein ␤ (C/ EBP␤) is responsible for influenza virus-infection mediated Fas up-regulation (44). In addition, NF-B and C/EBP consensus elements are suggested to be involved in rat Fas expression (45).…”
Section: Discussionmentioning
confidence: 99%
“…Although the death receptor-mediated apoptosis pathway induced by influenza infection has been extensively studied Wada et al, 1995;Fujimoto et al, 1998), little is known about the potential participation of the mitochondriamediated apoptosis pathway during influenza-induced cell death. Although PK-15 cells are not commonly used for swine influenza virus replication, our results shown in Figure 1 demonstrated that PK-15 cell was shown to fully support SIV replications.…”
Section: Discussionmentioning
confidence: 99%